Investigations on the synthesis, structural characterization and electrochemical properties of diiron azadithiolate complexes and phosphine-substituted derivatives. (15th October 2017) - Li, Yu-Long; Wu, Yu; Wei, Jian; Wei, Juan; Xie, Bin; Zou, Li-Ke; Cheng, Jie; Wang, Zheng; He, Jiao; Wu, Mei-Li; Zhao, Pei-Hua
Graphical abstract: Three diiron azadithiolate complexes Fe2 [( μ -SCH2 )2 NCH2 CH2 CH(CH3 )2 ](CO)6 (1 ), Fe2 [( μ -SCH2 )2 NCH(CH2 CH3 )2 ](CO)6 (2 ), Fe2 [( μ -SCH2 )2 NCH2 CH2 CH2 SCH3 ](CO)6 (3 ) and two phosphine-substituted complexes Fe2 [( μ -SCH2 )2 NCH2 CH2 CH(CH3 )2 ](CO)5 (dppm) (4 ), Fe2 [( μ -SCH2 )2 NCH(CH2 CH3 )2 ](CO)5 (dppm) (5 ) have been synthesized and characterized by elemental analysis, FTIR, and NMR ( 1 H, 13 C, 31 P) spectroscopies, and particularly for1 –3 by X-ray crystallography. Especially, complexes1 –5 were found to be catalysts for hydrogen production under electrochemical conditions. Abstract: Three novel diiron azadithiolate complexes Fe2 [( μ -SCH2 )2 NCH2 CH2 CH(CH3 )2 ](CO)6 (1 ), Fe2 [( μ -SCH2 )2 NCH(CH2 CH3 )2 ](CO)6 (2 ) and Fe2 [( μ -SCH2 )2 NCH2 CH2 CH2 SCH3 ](CO)6 (3 ) have been synthesized by treatment of Fe2 ( μ -SCH2 OH)2 (CO)6 with primary amines RNH2 (R = CH2 CH2 CH(CH3 )2, CH(CH2 CH3 )2, CH2 CH2 CH2 SCH3 ). Meanwhile, reaction of Fe2 ( μ -SCH2 OH)2 (CO)6 and diphosphine ligand Ph2 PCH2 PPh2 (dppm), followed by the addition of amines NH2 CH2 CH2 CH(CH3 )2 and NH2 CH(CH2 CH3 )2 resulted in the formation of the target phosphine-substituted diiron azadithiolate complexes Fe2 [( μ -SCH2 )2 NCH2 CH2 CH(CH3 )2 ](CO)5 (dppm) (4 ) and Fe2 [( μ -SCH2 )2 NCH(CH2 CH3 )2 ](CO)5 (dppm) (5 ). Complexes1 –5 have been fully characterized by elemental analysis, FTIR, and NMR ( 1 H, 13 C, 31 P) spectroscopies, and particularly for1 –3 by X-ray crystallography. In addition, complexes1 –5 were found to be catalysts for hydrogen production under electrochemical conditions.